LANGKAH PENGEMBANGAN MEDIA PEMBELAJARAN MACROMEDIA FLASH UNTUK PEMBELAJARAN MEMBUAT POLA DASAR BADAN SISTEM SOEN - Slamet Susanti (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2019)
The purpose of study was to find out the step to develop macromedia flash for learning or making the basic pattern of the soen’s system. This research is a type of development research. The development step uses the Puslijaknov Team theory which includes 5 stage:product analysis to be developed, the initial product development, expert validation and revision, small-scale and revisions, large-scale and final products. The research instrument uses observation sheets to reveal the use media in learning. Data analiasis technique uses descriptive analysis. Results showed the development of macromedia flash media through product analysis namely syllabus analysis and media needs analysis, developing the initial product namely the process making macromedia flash, expert validation to find out feasibility of media, small-scale of learning using macromedia flash which was observed 2 observers with good results, large-scale of implementation of learning using macromedia flash which was observed 2 observers with very good results.